2002
DOI: 10.1096/fj.01-0718hyp
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal ABCA1 expression contributes to the decrease in cholesterol absorption after plant stanol consumption

Abstract: The hypocholesterolemic effect of plant stanols is explained by a decreased intestinal cholesterol absorption due to a competition between plant stanols and cholesterol for incorporation into mixed micelles. Earlier we had suggested that plant stanols have a so far unknown action inside the enterocytes. The recent discovery of the involvement of ATP binding cassette (ABC) transporters in cholesterol absorption was a lead to further explore the hypocholesterolemic mechanism of plant stanols. We found that mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 32 publications
4
92
1
3
Order By: Relevance
“…Modified PS and stanols have been shown to modify the cholesterol influx and efflux from cells by altering nuclear hormone receptor activity, although it is still under discussion whether such a direct effect on the gene level can be considered one of the key mechanisms of action of PS (Plat and Mensink, 2002;Kaneko et al, 2003;Plosch et al, 2004;Calpe-Berdiel et al, 2005). The potential effect on nuclear hormone receptors could also influence gene expression of inflammatory mediators such as iNOS, COX-2 and IL-6 (Joseph et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Modified PS and stanols have been shown to modify the cholesterol influx and efflux from cells by altering nuclear hormone receptor activity, although it is still under discussion whether such a direct effect on the gene level can be considered one of the key mechanisms of action of PS (Plat and Mensink, 2002;Kaneko et al, 2003;Plosch et al, 2004;Calpe-Berdiel et al, 2005). The potential effect on nuclear hormone receptors could also influence gene expression of inflammatory mediators such as iNOS, COX-2 and IL-6 (Joseph et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The isolated cell pellet was taken up in 1500 ml Trizol (GIBCO, Invitrogen, Breda, The Netherlands) and immediately stored at -801C until further isolation according standard protocols. Following DNAse treatment (Promega Benelux B.V., Leiden, The Netherlands), cDNA was synthesized as described before (Plat and Mensink, 2002b). LDLreceptor mRNA expression was determined by real-time PCR.…”
Section: Ldl-receptor Mrnamentioning
confidence: 99%
“…The most likely explanation may be found in the primary location of the cholesterol-lowering effect, that is, the intestine. We have earlier hypothesized that the effect of plant sterols and stanols on cholesterol is because of the effects inside the enterocytes; most likely they increase cholesterol efflux back into the intestinal lumen (Plat and Mensink, 2002b). This can also occur in FH patients, as it does not involve LDL-receptor functioning.…”
Section: )mentioning
confidence: 99%
“…For ABCA1, a study using Caco-2 cells reported that application of mixed micelles enriched with sitostanol enhanced ABCA1 expression [24]; ABCA1 expression would be more sensitive to sitosterol in mammals. Expression level of abca1 was significantly higher in the sitosterol-fed group, in comparison to the no-sterol and the cholesterol-fed groups in this study.…”
Section: Discussionmentioning
confidence: 99%